Dynamic Load Sharing Characteristic of Planetary Transmission Considering Number of Planetary Wheel and Clearance - Dong Hao; Liu Zhiyu; Liu Bo (Jixie chuandong)
In order to study the influence of the number of planetary wheel and clearance on the dynamic load sharing characteristics of the planetary transmission system， based on the lumped parameter theory， considering the factors such as error， support stiffness， load and clearance， the dynamics model of the central wheel floating planetary transmission system is established. The model is solved by Runge-Kutta numerical method， and the relationship between the number of planetary wheel， the clearance and the load sharing characteristics is established. The results show that， with the change of the tooth flank clearance， the load sharing coefficient decreases rapidly and tend to be gentle， and the tooth flank clearance has a compensating effect， which reduces the uneven distribution caused by the increase of the planetary gears and improves the load sharing characteristics of the system. As the support clearance increases， the load sharing coefficient decreases almost at a constant speed， and the support clearance makes the system in a floating transmission state， which has better load sharing characteristics. When the torque is small， the system is highly sensitive to the clearance and can effectively alleviate the problem of uneven distribution caused by the error. As the torque increases， the error excitation is suppressed and the load sharing performance is improved.